Design and validation of a prognostic index of death from COVID-19: a prospective cohort - Alexis Álvarez Aliaga; Julio César González Aguilera; Alexis Suárez Quesada; Andrés José Quesada Vázquez; Liannys Lidia Naranjo Flores; Adonis Frómeta Guerra (Universidad de Ciencias Médicas de La Habana, 2024)
Introduction: COVID-19 caused high morbidity and mortality worldwide due to the lack of effective treatment and timely recognition of individuals with worse prognosis. Objective: To evaluate the capacity of the index to predict the risk of death in patients with covid-19, based on prognostic factors. Material and Methods: An analytical cohort study was carried out in patients with COVID-19 in the General Provincial Hospital "Carlos Manuel de Céspedes" of Bayamo municipality, Granma province, from January 1, 2020 to March 31, 2023. Results: Internal validity of the index was adequate with a sensitivity of 88.96%, specificity of 92.58% and a validity index of 91.22%. The discriminative capacity of the index (area under the ROC curve of 0.975) and the calibration (Hosmer and Lemeshow: p= 0.383) were appropriate. Conclusions: The predictive capacity and calibration of the index were adequate, as well as the accuracy and reliability, so it can be used as a clinical surveillance tool.